Relevansi Makna Sumpah Pemuda Dalam Menumbuhkan Semangat Nasionalisme - Rhenna May; Yoga Wahyu Ferniawan; Debi Setiawati (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
Sumpah Pemuda was read on October 28, 1928, as the final result of the Second Indonesian Youth Congress meeting, which until now is usually commemorated every year with the birth of Sumpah Pemuda,, which is one of the important milestones in the history of the Indonesian nation's struggle. In the current era, what role does the meaning of the youth oath play in fostering the spirit of nationalism? Where nationalism itself is a manifestation of his love for his own country. This article was created to find out what the relevance of the meaning of the youth oath is in fostering a spirit of nationalism and, among them, being proud to speak Indonesian, teaching the values of unity so as to avoid issues of sara, fostering a sense of love for the motherland, etc. This article uses a qualitative approach with historical research methods and data collection techniques using literature studies taken based on keywords carried out from various scientific reference sources, journals, Google Books, and other online sources. The Youth Pledge, which is annually commemorated on October 28 and was established in 1928, has such a deep meaning for the Indonesian nation because of its fruitful struggle where there is Indonesian unity, one language, namely Indonesian, and pride in being part of the Indonesian state. It is fitting that today's young generation continue the struggle for Sumpah Pemuda with their spirit of nationalism. So that Indonesian identity is not lost and is not easily influenced by bad influences from other nations. Nationalism itself is a form of love for one's nation. By doing various things, including upholding unity by respecting others, upholding tolerance, and not being affected by issues of sara and hoaxes, especially in the increasingly widespread digital era, being proud to speak Indonesian can be applied by learning to use proper spelling, always using formal events, loving domestic products, and wearing batik and the work of the nation's children in the form of clothes, shoes, and other necessities, as well as helping to preserve the culture of the country and region of origin. These things should be introduced and taught to the younger generation today and in the future so that their sustainability is maintained and can be enjoyed by the general public in their own countries and abroad.